Minor Characters’ Influences on Belly’s Emotional Maturity in Jenny Han’s The Summer I Turned Pretty - Merry Christiana; Maria Vincentia Eka Mulatsih (Indonesian Journal of English Language Studies (IJELS), 2025)
Emotional maturity plays a significant role in the behavior of individuals. Jenny Han’s novel The Summer I Turned Pretty depicts emotional maturity through its characters. This study aims to analyze the influences of minor characters on the main character’s emotional maturity, formulated through the question: “What are the influences that the minor characters bring toward Belly’s emotional maturity?”. To answer the question, the writers applied the theory of emotional maturity. This study employed the New Criticism approach along with the close reading method, as it dealt with the theory of emotional maturity. Data were collected using a library research technique, in which the novel served as a primary source, while supporting books, journals, and articles were used as secondary sources. The findings of this study revealed that Conrad, Jeremiah, and Susannah, as the minor characters, significantly influenced Belly’s emotional maturity. Belly underwent five levels of FitzMaurice’s emotional maturity, namely:  emotional responsibility, honesty, openness, assertiveness, and understanding. These five levels of emotional maturity experienced by Belly were influenced by Conrad, Jeremiah, and Susannah. By understanding the development of Belly’s emotional maturity, the readers can reflect on themselves and apply the positive behaviors exhibited by Belly.